2005
DOI: 10.1007/s10653-005-3991-x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in groundwaters of the Lower Mekong

Abstract: Increasing incidence and awareness of arsenic in many alluvial aquifers of South-east Asia has raised concern over possible arsenic in the Lower Mekong Basin. Here, we have undertaken new research and reviewed many previous small-scale studies to provide a comprehensive overview of the status of arsenic in aquifers of Cambodia and the Cuu Long Delta of Vietnam. In general natural arsenic originates from the Upper Mekong basin, rather than from the local geology, and is widespread in soils at typical concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 16 publications
1
34
1
Order By: Relevance
“…In this study, some samples (3/14) were collected from deep wells with a depth of over 300 m, and other samples (11/14) were collected from shallow wells with a depth of about 30 to 60 m. In general, a high concentration of As has been observed in shallow aquifers. [7][8][9] Consistent with this, some samples collected from shallow wells were contaminated with a high concentration of As, whereas samples collected from deep wells were not. In addition, the average number of shallow-well groups had significantly higher concentrations of Mn, Ba, Ca, and Mg than those of the deep-well groups (Table 1).…”
Section: Fig 3 Concentration Of Mn (A) and Ba (B) In The Groundwatermentioning
confidence: 60%
See 1 more Smart Citation
“…In this study, some samples (3/14) were collected from deep wells with a depth of over 300 m, and other samples (11/14) were collected from shallow wells with a depth of about 30 to 60 m. In general, a high concentration of As has been observed in shallow aquifers. [7][8][9] Consistent with this, some samples collected from shallow wells were contaminated with a high concentration of As, whereas samples collected from deep wells were not. In addition, the average number of shallow-well groups had significantly higher concentrations of Mn, Ba, Ca, and Mg than those of the deep-well groups (Table 1).…”
Section: Fig 3 Concentration Of Mn (A) and Ba (B) In The Groundwatermentioning
confidence: 60%
“…In regard to the Mekong River Delta, Stanger et al recently reported on As pollution in groundwater collected from the lower Mekong basin. 7) To our knowledge, however, a study of contamination by multiple elements in the Mekong River Delta has not been reported.…”
Section: Introductionmentioning
confidence: 91%
“…1). Whereas prior synoptic studies in the Delta have focused on near-river areas, where the highest population densities and arsenic concentrations are found (14)(15)(16)(17)(18), wells in this new survey were sampled in proportion to their abundance in all populated areas, providing unprecedented spatial coverage. Our analysis uses (i) the richness of these observations along with (ii) simulation of the spatiotemporally explicit flow and pumping history of the multiaquifer system and (iii) validation of pumping-induced compaction by radar remote sensing of land subsidence.…”
mentioning
confidence: 99%
“…In Cambodia, the natural arsenic originates from the upper Mekong basin, and is widespread in soils. Within the lower Mekong delta, 5.7% of all groundwater samples exceeded 50 μg/L, while 12.9% exceeded 10 μg/L (Stagner et al, 2005). A small-scale health survey conducted in Myanmar in 2002 reported that 66.6% of the water samples from wells have arsenic levels of >50 μg/L (Tun, et al, 2002).…”
Section: Introductionmentioning
confidence: 99%